Peran Perpustakaan Desa Sebagai Sumber Informasi Masyarakat di Kecamatan Bathin III Kabupaten Bungo - Rahmawati, Saummi; Haqqi, Athiatul; Ramayanti, Rory (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research aims to reveal the role of the Purwo Bakti Hamlet library as a source of community information in Bathin III District, Bungo Regency, the obstacles faced by the Purwo Bakti Hamlet Library as a source of community information in Bathin III District, Bungo Regency and the efforts that can be made by the Purwo Bakti Hamlet Library as a source. community information in Bathin III District, Bungo Regency. This thesis uses a qualitative method approach with a descriptive approach to data collection through observation, interviews and documentation. Based on the research carried out, the following results were obtained: first, the role of the Purwo Bakti Hamlet library as a source of information for the community in Bathin III District, Bungo Regency, including a learning resource center for the Purwo Bakti Hamlet community, where catfish and tilapia fish training was carried out, training on slicing bananas for sale. ,as a catalyst for change in reading culture for the people of Purwo Bakti Hamlet, as an agent of social change from children to adults and as a communication bridge between the community and the government to advance the welfare of the people of Purwo Bakti Hamlet; secondly, the obstacles faced by the Purwo Bakti Hamlet library as sources of public information in Bathin III District, Bungo Regency, including the lack of community participation in utilizing the Purwo Bakti Hamlet library, limited human resource capabilities in utilizing the latest technology and the lack of library facilities and infrastructure to be updated from references and collections; third, efforts that can The Dusun Purwo Bakti library is carried out as a source of information for the community in Bathin III District, Bungo Regency, including holding training for human resources by bringing in speakers from the district to share information and provide facilities and infrastructure, as well as holding promotions to the community through community activities. Keywords: Role, village library, community information source